Pengaruh Beasiswa KIP-K Terhadap Prestasi Belajar Mahasiswa Manajemen Pendidikan Angkatan 2021 Universitas Negeri Surabaya - Sabrina Fitri Jasmine (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The high cost of education in Indonesia makes it difficult for people from the middle to lower economic classes to continue their education to a higher level. Due to budget constraints, many students decide not to continue their education to a higher level. The Indonesian government seeks a solution to deal with this problem by providing a financial assistance program in the form of KIP-K scholarships to outstanding students from the middle to lower economic classes. The KIP-K scholarship program also seeks to develop quality human resources. One of them is registered in the Education Management study program at Surabaya State University. The purpose of this study was to determine whether the provision of KIP-K scholarships has an impact on the academic performance of Surabaya State University students class of 2021 enrolled in the Education Management study program. This study uses quantitative research methods with data collection techniques in the form of questionnaires. Data analysis techniques use normality test calculations, T tests and simple regression analysis. The results of the study state that there is an influence between the provision of KIP-K scholarships on the learning achievement of Surabaya State University Education Management students class of 2021, with a coefficient value of 54.1%.